The Relative Earnings of Visible Minorities in Canada: New Evidence from the 1996 Census - Swidinsky, Robert; Swidinsky, Michael (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2002)
SummaryThis article presents new evidence on the relative earnings of visible minority immigrant and native-born paid workers in Canada using data from the 1996 Census. Our findings show that labour market disadvantages associated with visible minority status are largely confined to immigrant men. The earnings deficits imputed to minority native-born men and immigrant women are fairly modest, and it appears that native-born women are paid a premium. Among immigrant men, labour market disadvantages are apparent primarily among those who were older when they arrived in Canada. There is some evidence that foreign work experience is relatively undervalued, but there is little evidence that immigrants receive lower compensation for foreign-based schooling. Finally, our analysis of individual ethnic minority groups reveals that Black men are most profoundly affected by labour market discrimination: The earnings deficit they must contend with is both significant and inter-generationally persistent.